Correction to: The epidemiological characteristics of deaths with COVID-19 in the early stage of epidemic in Wuhan, China - Jianjun Bai; Fang Shi; Jinhong Cao; Haoyu Wen; Fang Wang; Sumaira Mubarik; Xiaoxue Liu; Yong Yu; Jianbo Ding; Chuanhua Yu (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.